2020
DOI: 10.1111/gcb.15024
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall manipulation experiments as simulated by terrestrial biosphere models: Where do we stand?

Abstract: Changes in rainfall amounts and patterns have been observed and are expected to continue in the near future with potentially significant ecological and societal consequences. Modelling vegetation responses to changes in rainfall is thus crucial to project water and carbon cycles in the future. In this study, we present the results of a new model-data intercomparison project, where we tested the ability of 10 terrestrial biosphere models to reproduce the observed sensitivity of ecosystem productivity to rainfal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
70
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(83 citation statements)
references
References 138 publications
1
70
2
Order By: Relevance
“…Water stress on ecosystem productivity in the satellite observations was estimated based on the atmospheric water demand (i.e., vapor pressure deficit) but not water supply (i.e., soil water availability; W. Smith et al, ), while the TBMs in this study included more sophisticated mechanisms to represent soil water stresses by considering water supply and demand (e.g., Ito & Inatomi, ; Krinner et al, ; Zeng et al, ). Previous studies have reported that the lack of dynamic root growth, hydrological redistribution, groundwater movement, and reasonable carbon allocation during droughts in models are potential causes responsible for larger estimation of vegetation response to water deficit (Hu et al, ; Li et al, ; Paschalis et al, ). For example, during Amazon droughts, trees can increase water use efficiency and uptake water from aquifer through deep roots to mitigate drought impacts (Goll et al, ; Yang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Water stress on ecosystem productivity in the satellite observations was estimated based on the atmospheric water demand (i.e., vapor pressure deficit) but not water supply (i.e., soil water availability; W. Smith et al, ), while the TBMs in this study included more sophisticated mechanisms to represent soil water stresses by considering water supply and demand (e.g., Ito & Inatomi, ; Krinner et al, ; Zeng et al, ). Previous studies have reported that the lack of dynamic root growth, hydrological redistribution, groundwater movement, and reasonable carbon allocation during droughts in models are potential causes responsible for larger estimation of vegetation response to water deficit (Hu et al, ; Li et al, ; Paschalis et al, ). For example, during Amazon droughts, trees can increase water use efficiency and uptake water from aquifer through deep roots to mitigate drought impacts (Goll et al, ; Yang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Changes in rainfall regime are occurring worldwide 4,5 and have substantial consequences for vertebrate population dynamics, the species composition of communities and ecosystem functions and services 6,7 .…”
Section: Main Textmentioning
confidence: 99%
“…Rainfall manipulation experiments are among our best physical approximations of future scenarios and serve as important benchmarks for measuring the performance of terrestrial biosphere models. By synthesizing results from rainfall manipulation experiments across a range of biomes and environments, a new study by Paschalis et al (2020) diagnoses current limitations in model structure, identifies new data needs, and provides lessons for future model development.…”
mentioning
confidence: 99%
“…Thus, translating rainfall into ecosystem‐level water, energy, and carbon fluxes is a nontrivial and cross‐scale process, with the effects of rainfall at various spatial scales typically captured within terrestrial biosphere models by coupling a land surface scheme with a hydrological modeling component and a dynamic vegetation module. The main question that drives Paschalis et al (2020) is whether ecosystem responses to rainfall variability—subject to all the scaling challenges above—have been adequately represented within terrestrial biosphere models. This is done by synthesizing results from 10 terrestrial ecosystem models applied to rainfall manipulation experiments at a number of sites spanning a wide range of biomes and environments.…”
mentioning
confidence: 99%
See 1 more Smart Citation